Discourse features of lyrics in american patriotic songs - Văn,Thị Bạch Giang. (2016)
This thesis is mainly aimed at examining discourse features of lyrics in American Patriotic songs (LAPSs). The data of the study are 46 samples - 46 songs collected from two prestigious songbooks in the United States. The data were described and analyzed in terms of discourse features under qualitative and quantitative approaches. The thesis is an attempt to figure out some commonly used linguistic features in LAPSs in terms of syntactic features, semantic fields, lexical choices and stylistic devices in the views of Quirk et al. (1985) and Galperin (1977) in their books entitled A Comprehensive Grammar of the English Language and Stylistics respectively. The findings of this study show that relative clauses, imperative sentences and sentence types are commonly used in LAPSs for the purpose of embracing the breath- taking beauty of America, the strong love to this nation, the unyielding spirit of the American people. Moreover, the use of apostrophes makes the lyrics more appealing and interesting. Besides, the use of stylistic devices makes the language in LAPSs sound colorful, vivid and arresting. It is hoped that the results of this study will probably provide some practical applications for the teaching and learning of English. This study may also be useful to those who are interested in music, especially in American patriotic songs.